Bank BTPN’s Financial Performance Before and After Jenius as a Digital Banking Product - Pamungkas, Fajar; Suryaningsum, Sri; Satria N, Hari Kusuma (AIBPM Publisher, 2022)
ABSTRACT Jenius from BTPN has attracted many customers and continues to grow every year. However, further research is needed to see the positive impact of Jenius on Bank BTPN's financial performance. Therefore, this study was conducted to test the differences of BTPN’s financial performance before and after launching Jenius digital bank products. This study uses CAMELS indicator as the proxy of financial performance. The sample is selected by using purposive sampling method. The criteria used to obtain the sample the annual reports of Bank BTPN before launching Jenius (2013-2015) and after launching Jenius (2017-2019). Based on these criteria, a sample of 3 annual reports of Bank BTPN before launching Jenius and 3 annual financial statements of Bank BTPN after launching Jenius is obtained. The paired t-test method was employed to examine the data by using SPSS25 software.The Jenius digital banking product is one of many BTPN products. When Jenius was first introduced, it was able to attract the enthusiasm of customers, especially young customers because digital devices are part of their daily life. Jenius could not improve Bank BTPN’s financial performance significantly because it was just one of their products. This was also because most people are not yet familiar enough with digital banking. Based on the analysis that has been carried out using the t-test, the results obtained are not the same across all the variables tested. The results of this study indicate that there are significant differences between the NPL and BOPO values of Bank BTPN. Meanwhile, other variables such as CAR, ROE, LDR, and risk-weighted assets according to Bank BTPN before and after launching Jenius digital bank products, there is no significant difference. Jenius needs to be appreciated because it has become the role model for digital education for banking users since it was first launched in 2016.Keywords: Digital Banking; Financial performance; CAMELS; BTPN; Jenius